Perencanaan Kota dan Pengelolaan Air: Pengaruh Pembangunan terhadap Kualitas Air Sungai Cisadane di Banksasuci, Cihuni, Tangerang - Lia Wulandari; R. Maisa Yudono; Hesti Rosdiana; Yuni Hariyanti (Karawo : Journal of Community Service (KJCS), 2026)
This community service activity was carried out on 21 September 2024 at Banksasuci (Bank Sampah Sungai Cisadane), Cihuni, Gading Serpong, Tangerang Regency, as part of the SOUL PROJECT (Save Our Earth With Law) organized by the Student Executive Board of the Faculty of Law, UPN Veteran Jakarta. The program focused on urban planning and water management in relation to the impact of development on Cisadane River water quality. The Cisadane River is one of the most vital water sources in Banten Province, supplying raw water for PDAM, agriculture, fisheries, and industry. However, rapid urbanization—marked by dense residential sprawl and industrial expansion—has caused a significant and sustained decline in river water quality. Research shows that COD and BOD concentrations in the Cisadane River trended upward continuously from 2005 to 2012, driven by industrial effluents concentrated in Jatiuwung and domestic wastewater from slum settlements. Institutional management of the river remains fragmented across multiple agencies at city, provincial, and national levels with weak coordination. This activity engaged approximately 50 participants through legal education sessions, participatory field discussions, river cleaning, and tree-planting activities. Results indicate a significant increase in participant awareness of the link between spatial planning, infrastructure development, and river water quality. This program recommends integrated spatial governance and community-based monitoring as key strategies for protecting the Cisadane River ecosystem.